CARACTERIZAÇÃO DA PERFORMANCE HIDRÁULICA DE DOIS EMISSORES TIPO MICROASPERSOR1 - Matos, José De Arimatea De; Ragoso, Carlos Renato Alves [UNESP] (Departamento de Engenharia Agrícola - UFCG, 1997)
The hydraulic characteristics of two trickle irrigation emitters, type micro-sprinkler Carborundum, model MSIII, were evaluated by analyzing the manufacturing variation coefficient and pressure discharge relationship. According to the ASAE classification, in relation to the manufacturing variation coefficient, the evaluated micro-sprinkler are considered as average. With the data obtained from the discharge versus pressure, the characteristic equation of each micro-sprinkler was found. The one with light green socket presented an equation q = 6.9235H0.3804, with a determination coefficient (R2) equal to 0.98 and flow regime considered completely turbulent. The one with pink socket presented an equation q=28.78H0.0853, with R2 equal to 0.80 and, according to the exponent discharge value, it is considered as self-compensating. About the hysteresis phenomenon, its amplitude was considered negligible.

Avaliaram-se as características hidráulicas de dois emissores de irrigação localizada, tipo micoraspersor Carborundum, modelo MSIII, tendo sido analisados o coeficiente de variação de fabricação e a equação característica da relação vazão-pressão. De acordo com a classificação da ASAE, quanto ao coeficiente de variação de fabricação os microaspersores avaliados são considerados médio. Com os dados obtidos da relação de vazão versus pressão encontrou-se a equação característica de cada microaspersor. O de bocal verde claro apresentou a quação q = 6,9235H0,3804, com coeficiente de determinação (R2) de 0,98 e regime de fluxo considerado plenamente turbulento. O de bocal rosa apresentou equação q = 28,78H0,0853, com um R2 igual a 0,80 e, de acordo com seu expoente de descarga, é considerado auto-compensante; quanto ao fenômeno de histerese, sua amplitude foi considerada desprezível.
HYDRAULIC PERFORMANCE CHARACTERIZATION OF TWO MICROSPRINKLER TYPE DRIPPERS
Keywords: hydraulic characteristics; trickle irrigation; micro-sprinkler; características hidráulicas; irrigação localizada; microaspersor